1986
DOI: 10.1007/bf00869258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus in elderly men aged 65 to 84 years in eastern and western Finland

Abstract: Summary.We studied the prevalence of diabetes mellitus in men aged 65 to 84 years in Finland. The study sample consisted of 763 men, the survivors of the Finnish cohort of the "Seven Countries Study" first examined in 1959. The participation rate in the present survey was 94%. Blood glucose, fasting and 2 h after a 75-g oral glucose load, was determined from capillary blood. Current WHO criteria for diabetes mellitus were used. The mean fasting blood glucose level, adjusted for age and body mass index, was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 32 publications
10
27
0
1
Order By: Relevance
“…This overall prevalence appears similar to the most recent prevalence figures of some northern European countries, accounting for about 4% [7][8][9][10][11] while it appears lower than in Malta (9.2 % for males and 14.5 % for females in the age 45-64 years), which provides the sole comparable data in southern Europe [1].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This overall prevalence appears similar to the most recent prevalence figures of some northern European countries, accounting for about 4% [7][8][9][10][11] while it appears lower than in Malta (9.2 % for males and 14.5 % for females in the age 45-64 years), which provides the sole comparable data in southern Europe [1].…”
Section: Discussionsupporting
confidence: 84%
“…As far as the relationship between diagnosed and undiagnosed diabetes is concerned, the available data show that the proportion of unknown diabetes exhibits great variation among different countries [9,11,[14][15][16][17][18][19], particularly when different Health Systems are operating. In our study its proportion resulted much lower with respect to the figures of 1 to 1 [14], up to now adopted in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Between studies with a different study design -using oral glucose tolerance tests or based on self report or general practice registers -the large proportion of patients with type 2 diabetes that is presumed to be undiagnosed (and could be as high as 50%) [10,11] can give rise to varying findings, especially because this proportion again may vary between regions or countries. Not only national but also international literature presents few publications with detailed data on the highest age categories: these publications are difficult to compare because of considerable differences in definitions and study design, and they show highly varying prevalence rates [12][13][14][15][16][17][18][19]. As the prevalence of type 2 diabetes increases quickly and is estimated to be highest in the eldest age categories, we consider it important not to ignore this age category and to present actual data on current prevalence, incidence and mortality of known diabetes in all age groups, including these eldest.…”
Section: Introductionmentioning
confidence: 99%
“…38 Some studies have reported that a large proportion of elderly subjects aged 65 years and over have either impaired glucose tolerance or overt diabetes. 39,40 In the case of all three variables we have observed an increase in mean values in smokers (cases) as compared to non-smokers (controls) in every age group. However, a strong correlation between smoking and the observed increase exists only in the case of HbA1c ('p-value' almost equal to 0.05 in 61-70 years age group and < 0.05 in all other age groups).…”
Section: Discussionmentioning
confidence: 58%